IMRT reirradiation with concurrent cetuximab immunotherapy in recurrent head and neck cancer - Zwicker, Felix; Röder, Falk; Thieke, Christian; Timke, Carmen; Münter, Marc; Huber, Peter E.; Debus, Jürgen (Strahlentherapie und Onkologie, 2011)
Purpose: In this retrospective investigation, the outcome and toxicity after reirradiation with concurrent cetuximab immunotherapyof recurrent head and neck cancer (HNC) in patients who had contraindications to platinum-based chemotherapy wereanalyzed. - Materials and methods: Ten patients with locally advanced recurrent HNC were retrospectively evaluated. In 9 cases, histology was squamous cell carcinoma, in one case adenoid cystic carcinoma. External beam radiotherapy was part of the initial treatment in all cases. Reirradiation was carried out using step-and-shoot intensity-modulated radiotherapy (IMRT) with a median dose of 50.4 Gy. Cetuximab was applied as loading dose (400 mg/m2) 1 week prior to reirradiation and then weekly concurrently with radiotherapy (250 mg/m2). - Results: The median overall survival time after initiation of reirradiation was 7 months; the 1-year overall survival (OS) rate was 40%. Local failure was found in 3 patients, resulting in a 1-year local control (LC) rate of 61%. The 1-year locoregional control (LRC) rate was 44%, while the 1-year distant metastasis-free survival (DMFS) was 75%. Acute hematological toxicity was not observed in the group. Severe acute toxicity included one fatal infield arterial bleeding and one flap necrosis. Severe late toxicities were noted in 2 patients: fibrosis of the temporomandibular joint in 1 patient and stenosis of the cervical esophagus in another. Conclusions: IMRT reirradiation with concurrent cetuximab immunotherapy in recurrent HNC is feasible with acceptable acute toxicity. Further investigations are necessary to determine the clinical role of this therapy concept.
Published online: December 23, 2010
Gesehen am 30.01.2023